EFFICACY AND SAFETY OF REGDANVIMAB THERAPY IN MODERATE COURSE OF COVID-19 - Михаил Исаакович Ликстанов; Ирина Николаевна Кушнир; Анна Владимировна Ромасюк; Ирина Анатольевна Хмелева; Екатерина Александровна Власова; Мария Сергеевна Маталасова; Татьяна Владимировна Шофорусь; Мария Геннадьевна Якушенко; Елена Владимировна Стрельцова; Павел Аскандерович Аскандеров; Вадим Гельевич Мозес; Евгения Юрьевна Рисовер; et al. (Медицина в Кузбассе, 2023)
The efficacy and safety of therapy with a human monoclonal antibody (international patent name Regdanvimab) in patients with a moderate course of COVID-19 was evaluated. A total of 41 patients (48.8 % women and 51.2 % men) were treated during the period of mixed distribution of delta and omicron strains of SARS-CoV-2. Regdanvimab was administered in a hospital setting based on the calculation of the amount of 40 mg/kg per patient's body weight. The median dose of regdanvimab was 3200 (2720; 4000) mg, the minimum dose was 2040 mg, and the maximum dose was 4800 mg.